2009
DOI: 10.1038/ng.364
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at ten loci influence QT interval duration in the QTGEN Study

Abstract: QT interval duration reflecting myocardial repolarization on the electrocardiogram is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of 3 genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study. We observed associations at P < 5×10−8 with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
367
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(391 citation statements)
references
References 43 publications
22
367
2
Order By: Relevance
“…34 The NOS1AP association was further substantiated by two later GWAS in a large sample set of nearly 30 000 samples for the initial and replication studies. 35,36 Besides confirming the previously known gene, several new loci were also identified. Interestingly, both studies also found KCNQ1 to be associated with the trait; this is because the gene was also associated with type-2 diabetes (T2D).…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firsupporting
confidence: 68%
“…34 The NOS1AP association was further substantiated by two later GWAS in a large sample set of nearly 30 000 samples for the initial and replication studies. 35,36 Besides confirming the previously known gene, several new loci were also identified. Interestingly, both studies also found KCNQ1 to be associated with the trait; this is because the gene was also associated with type-2 diabetes (T2D).…”
Section: Gwas After Hapmap-the Progress Over the Past 5 Years The Firsupporting
confidence: 68%
“…The SNP rs846111 actually lies within the open reading frame of the RNF207 gene and not in its 3Ј untranslated region as reported (10,11). Interestingly, RNF207 contains a RING domain (17), suggesting that the protein may be a ubiquitin ligase.…”
mentioning
confidence: 82%
“…One SNP associated with prolongation of the QT interval (approximately 1.7 (10, 11) or 2.9 ms (16)) has been mapped within the gene encoding RNF207 (10,11). The SNP rs846111 actually lies within the open reading frame of the RNF207 gene and not in its 3Ј untranslated region as reported (10,11).…”
mentioning
confidence: 86%
See 2 more Smart Citations